Intercity Rail Maintainability Analysis: A Case Study on Rolling Stock Maintenance Compliance - Baharin, Nuramira Najihah; Sanusi, Shahmir Hayyan; Abdul Hamid, Nor Aziati; Jumiran, Amirul Afif (Journal of Advanced Mechanical Engineering Applications, 2022)
Compliance to organizational standard is essential for maintaining high work performance within the appropriate timescale which can result in reduction of maintenance expenses. The purpose of this study was to analyze the compliance level of preventive maintenance activities based on job frequency and its working hours. Historical data of preventive maintenance from 2019 - 2020 obtained from a field study at Keretapi Tanah Melayu Berhad (KTMB) Depot Batu Gajah, Perak, was analyzed to investigate the frequency, manhours, and the cost involved for each type of preventive maintenance activities namely Exam A, B C and D involving ETS Class 91. From the results, Exam A contributed to the highest non-compliance practice compared to the other Exam where the highest non-compliance percentage (62%) was recorded in 2020 which results in losses of RM RM2,552.82. This study is beneficial for the organization as it determine irregular downtime and manhours compliance for rolling stock system maintenance in order to shape for a better future maintenance plan that will results in efficient operation and higher revenue.